Nutrient Signaling and Lysosome Positioning Crosstalk Through a Multifunctional Protein, Folliculin - de Martín Garrido, Natàlia; Aylett, Christopher H. S. (Frontiers in Cell and Developmental Biology, 2020)
FLCN was identified as the gene responsible for Birt-Hogg-Dubé (BHD) syndrome, a hereditary syndrome associated with the appearance of familiar renal oncocytomas. Most mutations affecting FLCN result in the truncation of the protein, and therefore loss of its associated functions, as typical for a tumour suppressor. FLCN encodes the protein folliculin (FLCN), which is involved in numerous biological processes; mutations affecting this protein thus lead to different phenotypes depending on the cellular context. FLCN forms complexes with two large interacting proteins, FNIP1 and FNIP2. Structural studies have shown that both FLCN and FNIPs contain longin and differentially expressed in normal versus neoplastic cells (DENN) domains, typically involved in the regulation of small GTPases. Accordingly, functional studies show that FLCN regulates both the Rag and the Rab GTPases depending on nutrient availability, which are respectively involved in the mTORC1 pathway and lysosomal positioning. Although recent structural studies shed light on the precise mechanism by which FLCN regulates the Rag GTPases, which in turn regulate mTORC1, how FLCN regulates membrane trafficking through the Rab GTPases or the significance of the intriguing FLCN-FNIP-AMPK complex formation are questions that still remain unanswered. We discuss the recent progress in our understanding of FLCN regulation of both growth signalling and lysosomal positioning, as well as future approaches to establish detailed mechanisms to explain the disparate phenotypes caused by the loss of FLCN function and the development of BHD-associated and other tumours.